Enhancing Resilience in Indonesian Firms: Integrating ERM, Organizational Ambidexterity, and Strategic Renewal Post-COVID-19 - Budi Chandra; Teddy Jurnali; Sheila Septiany (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The COVID-19 pandemic fundamentally disrupted global business environments and intensified uncertainty, compelling firms to rapidly adapt their strategies and capabilities to maintain resilience and competitiveness in increasingly volatile and complex markets. This study aims to investigate the mediating role of strategic renewal in the relationship between corporate governance mechanisms, enterprise risk management, organizational ambidexterity, and firm performance. Using a sample of firms in Indonesia, the proposed model was tested employing Structural Equation Modeling (SEM). Data were obtained through questionnaires distributed to respondents, with a total of 377 valid responses used for the analysis. The findings reveal that enterprise risk management, as a governance mechanism, significantly enhances firm performance directly, while organizational ambidexterity also has a significant direct effect on firm performance. Additionally, organizational ambidexterity shows a significant positive relationship with strategic renewal, which in turn significantly impacts firm performance. These results underscore the critical importance of strategic renewal in amplifying the benefits of governance-based dynamic capabilities such as enterprise risk management and organizational ambidexterity for performance gains. This study highlights the need to integrate governance and dynamic capabilities through continuous strategic renewal processes to sustain competitive advantage in rapidly changing business environments, offering valuable insights for both academics and practitioners.